2015
DOI: 10.4103/1119-3077.170823
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in newer assisted reproductive technologies: A view from Nigeria

Abstract: There is an urgent need for stakeholders in developing countries to formulate cultural and context-specific guidelines to help address some of these ethical dilemmas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…According to few similar studies from other nations ( Brazil South Africa and Nigeria ), ART is predominantly private sector driven, expensive and remains unaffordable for those in need. [9][10][11] This is not in accordance with the findings from developed nations ( European countries ) where a specific number of cycles of IVF treatment are reimbursed by their governments.…”
Section: Discussioncontrasting
confidence: 56%
“…According to few similar studies from other nations ( Brazil South Africa and Nigeria ), ART is predominantly private sector driven, expensive and remains unaffordable for those in need. [9][10][11] This is not in accordance with the findings from developed nations ( European countries ) where a specific number of cycles of IVF treatment are reimbursed by their governments.…”
Section: Discussioncontrasting
confidence: 56%
“…This is due to the transfer of multiple embryos to the uterus to ascertain that at least one or two survive and develop until birth. [11,13] The present study revealed that the participants had good perception of ART techniques and their related ethical and legal issues. This finding corresponds with the study conducted in a developed country in the year 2012.…”
Section: [12]mentioning
confidence: 56%
“…In fact, few studies cited that the regulatory component for assisted reproduction is often overlooked or missing, despite the provision of ART [ 57 , 58 ]. Moreover, ART clinics usually adopt their own rules, which leads to different standards of care [ 59 ], contributes to inequality in access, and may facilitate professional liberty, with medical protocols not always in line with evidence-based standards or adapted to the needs of patients [ 60 ].…”
Section: Discussionmentioning
confidence: 99%